Molecular phylogeny of tribe Schismatoglottideae (Araceae) based on two plastid markers and recognition of a new tribe, Philonotieae, from the neotropics - Sin, Y.W; Boyce, P.C; Ahmad S., Othman; Leaw, CP (International Association for Plant Taxonomy, 2010)
Tribe Schismatoglottideae comprises one large genus, Schismatoglottis, and six small ‘satellite’ genera. A combined molecular phylogenetic analysis of matK, the 3′ portion of the trnK intron, and trnL-F sequence data was carried out on 77 taxa representing all genera in the tribe, all informal groups in Schismatoglottis, together with sister tribe Cryptocoryneae, and outgroups from Araceae. Analyses of combined datasets with parsimony, maximum likelihood, and Bayesian methods revealed tribe Schismatoglottideae to be a polyphyletic assemblage. Neotropical Schismatoglottis is shown to be sister to the palaeotropical Schismatoglottideae + Cryptocoryneae. Schismatoglottis acuminatissima is a sister clade to the rest of the Schismatoglottideae. Palaeotropical Schismatoglottis is unsupported as a monophyletic genus. A new neotropical tribe of Araceae, Philonotieae S.Y. Wong & P.C. Boyce, sister to Cryptocoryneae + palaeotropical Schismatoglottideae, is proposed.